Ernesto Nazareth - Carrasqueira, Maria José; Nazareth, Ernesto (Ybmusic, 2004)
1EponinaMaria José Carrasqueirafeat: Maria Jose Carrasqueira2OdeonMaria José Carrasqueirafeat: Maria Jose Carrasqueira3ElegantissimaMaria José Carrasqueirafeat: Maria Jose Carrasqueira4Coracao que SenteMaria José Carrasqueirafeat: Maria Jose CarrasqueiraSpotifyAmazon5Ouro Sobre AzulMaria José Carrasqueirafeat: Maria Jose CarrasqueiraSpotifyAmazon6VesperMaria José Carrasqueirafeat: Maria Jose Carrasqueira7EscorregandoMaria José Carrasqueirafeat: Maria Jose Carrasqueira8Turbilhao de BeijosMaria José Carrasqueirafeat: Maria Jose Carrasqueira9Apanhei-Te, CavaquinhoMaria José Carrasqueirafeat: Maria Jose CarrasqueiraSpotifyAmazon10ZeniteMaria José Carrasqueirafeat: Maria Jose Carrasqueira11ConfidenciasMaria José Carrasqueirafeat: Maria Jose Carrasqueira12Ameno ResedaMaria José Carrasqueirafeat: Maria Jose CarrasqueiraSpotify13ImprovisoMaria José Carrasqueirafeat: Maria Jose Carrasqueira14BatuqueMaria José Carrasqueirafeat: Maria Jose Carrasqueira15Fon -FonMaria José Carrasqueirafeat: Maria Jose Carrasqueira